The Moderating Role of Work Discipline on The Links Between Locus of Control and Work Ethics in Local Government Employees - Siswanto, Siswanto; Darus, Umi (MEC-J (Management and Economics Journal), 2020)
The aim of this study is to analyze the role of internal locus of control and external locus of control on work ethics. In addition, this study also analyzes the role of work discipline as a mediating variable. This study uses a quantitative approach. The number of research samples is 114 people. They are civil servants in the city government environment in East Java. Data analysis uses path analysis. The analysis shows that the two-locus of control variables have a positive effect on work ethics. Internal locus of control also has a positive effect on work discipline. Meanwhile, external locus of control does not affect work discipline. Analyst results show that work discipline has a role as a mediating variable. Meanwhile, in the external locus of control of work ethics, work discipline does not act as a mediating variable.